Rare Presentation of Left Lower Lobe Pulmonary Artery Dissection - René Hako; Ján Fedačko; Štefan Tóth; Radoslav Morochovič; Pavol Kristian; Tímea Pekárová; Petri Tuomainen; Daniel Pella (Case Reports in Medicine)
Background. Pulmonary arterial dissection with chronic pulmonary arterial hypertension as its major cause is a very rare but life-threatening condition. In most cases the main pulmonary trunk is the affected site usually without involvement of its branches. Segmental or lobar pulmonary artery dissection is extremely rare. Case Presentation. We report a unique case of left lower lobe pulmonary artery dissection in a 70-year-old male, with confirmed chronic pulmonary hypertension. To confirm dissection MDCT pulmonary angiography was used. Multiplanar reformation (MPR) images in sagittal, coronal, oblique sagittal, and curved projections were generated. This case report presents morphologic CT features of rare chronic left lobar pulmonary artery dissection associated with chronic pulmonary hypertension at a place of localised pulmonary artery calcification. CT pulmonary angiography excluded signs of thromboembolism and potential motion or flow artefacts. Conclusion. To the best of our knowledge, no case of lower lobe pulmonary artery dissection with flap calcification has been reported yet. CT imaging of the chest is a key diagnostic tool that is able to detect an intimal flap and a false lumen within the pulmonary arterial tree and is preferred in differential diagnosis of rare complications of sustained pulmonary arterial hypertension.